Exploring the Influence of Temperature on Aspects of the Reproductive Phenology of Temperate Seaweeds - de Bettignies, Thibaut; Wernberg, Thomas; Gurgel, C. Frederico D. (Frontiers in Marine Science, 2018)
As plants on land, seaweeds are likely to be susceptible to temperature-mediated changes in phenology such as shifts in their reproductive timing. With this review, we aimed to investigate the importance of temperature on reproductive phenophase transitions (i.e. maturation and release of propagules) of temperate seaweeds while discussing how global warming might affect their reproductive phenology. A systematic literature search returned a total of 81 relevant papers, which were reviewed for evidence of environmental, factors (including temperature) driving reproductive phenology. Only a few of studies reported effects of temperature on propagule release (spores and gametes). In contrast, reproductive maturation (both sporogenesis and gametogenesis) was found predominantly to be controlled by temperature. Our findings highlight the potential for phenological shifts in seaweeds in response to ocean warming. In contrast to the consistent advancement of spring events observed for terrestrial plants, there was evidence that warming can both advance and delay the timing of reproductive events for temperate seaweeds, especially the maturation of propagules. Because temperature was often found to act in combination with either day length or spectral composition, ocean warming might result in a mismatch between light and temperature requirements that could lead to reduced reproductive performance.